2012
DOI: 10.1108/13527601211247080
|View full text |Cite
|
Sign up to set email alerts
|

A new organisational memory for cross‐cultural knowledge management

Abstract: Purpose -Effectively managing the cultural environment is an important stepping stone towards international business success. Cultural problems, especially between partners coming from diametrically different cultural categories represent one of the key challenges of knowledge management in international business co-operations. The purpose of this paper is to investigate the influence of controversial cultural attitudes on collaboration and the use of most diverse knowledge capital of employees being regarded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Accordingly, in the context of intercultural training in global teams, Bartel‐Radic () concluded that long‐term intercultural interaction among employees facilitates the highest learning potential for intercultural competence. Participants will be able to recognize and use cultural differences as a resource for learning and designing effective actions according to each context (Ashdown, ; Sanchez Bengoa et al, ).…”
Section: Need For Practical Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, in the context of intercultural training in global teams, Bartel‐Radic () concluded that long‐term intercultural interaction among employees facilitates the highest learning potential for intercultural competence. Participants will be able to recognize and use cultural differences as a resource for learning and designing effective actions according to each context (Ashdown, ; Sanchez Bengoa et al, ).…”
Section: Need For Practical Experiencementioning
confidence: 99%
“…Ongoing trends toward immigration and globalization, for example, create heightened cultural concerns, leading most professionals to agree on the paramount role of multicultural competence (Dunn, Smith, & Montoya, ; Triandis, ; Vogelgesang, Clapp‐Smith, & Palmer, ). Furthermore, various developments in the field of modern information and communication technology, increasing cross‐border cooperations, and implicit knowledge management challenges (Sanchez Bengoa, Kaufmann, & Vrontis, ) expatriate missions or students becoming global travelers (Parham & Parham, ; Shaffer & Miller, ) have influenced the need for higher levels of cultural competence of leaders, managers, and students alike.…”
Section: Introductionmentioning
confidence: 99%
“…Each interview was transcribed, manually coded, analyzed and constantly compared with one another by the researchers who followed the three-step procedure of analysis to meet the requirements of the grounded theory approach (Hassi et al, 2011;Sánchez Bengoa et al, 2012). Firstly, the open coding was implemented to the data analysis, where the researchers were looking for common themes (keywords, phrases) emerging from the interviews (Randall and Mello, 2012).…”
Section: Research Aim and Methodsmentioning
confidence: 99%
“…In the mid-1990s learning in management theory evolved and was integrated in the knowledge management (KM) field that since then has received a considerable academic attention (Sánchez Bengoa, Kaufmann, & Vrontis, 2012). Knowledge can be perceived as a product of a learning process and learning as an acquisition of knowledge (Maruta, 2014), therefore the field indirectly addresses the learning issue.…”
Section: Knowledge Managementmentioning
confidence: 99%
“…It requires collection, distribution, and an efficient use of knowledge resources. Moreover, in view of proponents of the concept, KM enhances learning and performance in organisations (Sánchez Bengoa et al, 2012). Additionally, it can be anticipated that KM fosters OL and LO is a result of KM.…”
Section: Knowledge Managementmentioning
confidence: 99%